2006
DOI: 10.1007/s10067-006-0403-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of acute anterior uveitis with disease activity, functional ability and physical mobility in patients with ankylosing spondylitis: a cross-sectional study of Chinese patients in Taiwan

Abstract: Acute anterior uveitis (AAU) is the most frequently extra-articular manifestation of ankylosing spondylitis (AS). To investigate whether AAU has an association with disease activity, functional ability and physical mobility in AS patients, 146 Chinese AS patients in Taiwan were enrolled in a cross-sectional study. These patients fulfilled the 1984 modified New York criteria and visited the Outpatient Department of the Veterans General Hospital-Taipei from April 2004 to July 2005. Patients completed questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
2
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 11 publications
3
34
2
2
Order By: Relevance
“…Consistent with the results of other groups of investigators (9,38,39,48), our data emphasize the existence of elevated values of BASDAI and BASFI in AAU AS patients suggesting that these patients develop a more aggressive disease than wAAU AS patients. For the first time, we identified MMP-2/sCD147 ratio as a new variable to better characterize AAU AS patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with the results of other groups of investigators (9,38,39,48), our data emphasize the existence of elevated values of BASDAI and BASFI in AAU AS patients suggesting that these patients develop a more aggressive disease than wAAU AS patients. For the first time, we identified MMP-2/sCD147 ratio as a new variable to better characterize AAU AS patients.…”
Section: Discussionsupporting
confidence: 92%
“…This idea was generated by the observation that AAU AS patients seem to have a more rapid evolution of the disease (9). The results of Chen et al, on 146 Chinese AS patients in Taiwan, suggested that the presence of AAU in AS patients is associated with higher disease activity (BASDAI), poor functional ability and advanced physical impairment (BASFI) (38). Recently, another group of investigators showed on 159 patients with AS a relationship between the history of uveitis and AS disease activity (BASDAI) (not statistically significant) and functional impairment (BAS-FI) (statistically significant) (39).…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation could be that patients in trials were selected based on higher disease activity and that this may coincide with a higher prevalence of AAU. 24 Some limitations of the present study should be recognised. First, the prevalence of EAMs used in this review was usually not the main objective of the primary studies included, and therefore, not always indexed in the electronic article databases.…”
Section: Discussionmentioning
confidence: 84%
“…Chen et al 13 found an association between AAU and BAS-DAI. In the present study, no significant relationship between higher disease activity in AAU and SpA could be demonstrated statistically although a trend was found (P = 0.06).…”
Section: Discussionmentioning
confidence: 97%